INTERDISCIPLINARY DOCTORAL STUDIES AS A NEW EDUCATIONAL AND RESEARCH OPPORTUNITY IN LATVIA - Palkova, Karina; Kudeikina, Inga; Mihailovs, Ivans Jānis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Doctoral studies are the first stage of an academic career, which applies to both the academic doctoral study programme and the professional doctoral programme. Over the past two decades, the role and tasks of doctoral studies have changed dramatically, especially in Europe. Doctoral studies have become an important link between the European Higher Education Area and the European Research Area and its main task is to provide those with doctoral degrees with the best qualifications for the creation, implementation and diffusion of new knowledge and innovations. Interdisciplinarity is trending. Nowadays scientists, researchers, professionals face up with the global problems. This global problem usually is unsolvable and complex by individual fields of science. Therefore, interdisciplinarity is vital in educational process as well as n science. Interdisciplinary approach in thus field is challenging tasks for researchers and persons involved in educational process. Nevertheless, if Doctoral Programme is designed based on Interdisciplinarity, doctoral level studies in areas that cannot be accommodated in one of the departmental doctoral programs, could give broader and more unique research results. Interdisciplinary approach on doctoral level programme helps as well meet the individually designed interests or researcher. Bridging many disciplines together there is possible to provide novel and significant researches.